2014
DOI: 10.1095/biolreprod.113.110874
|View full text |Cite
|
Sign up to set email alerts
|

Gonad Differentiation in Zebrafish Is Regulated by the Canonical Wnt Signaling Pathway1

Abstract: Zebrafish males undergo a "juvenile ovary-to-testis" gonadal transformation process. Several genes, including nuclear receptor subfamily 5, group A (nr5a) and anti-Müllerian hormone (amh), and pathways such as Tp53-mediated germ-cell apoptosis have been implicated in zebrafish testis formation. However, our knowledge of the regulation of this complex process is incomplete, and much remains to be investigated about the molecular pathways and network of genes that control it. Using a microarray-based analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
56
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 85 publications
8
56
0
Order By: Relevance
“…In fish, masculinization by elevated temperature usually involves down-regulation of profemale genes, such as cyp19a1a and foxl2, and up-regulation of promale genes, such as dmrt1 or amh (8)(9)(10)(11)(12)(13)(14). In accordance with this general pattern, the FHT2 females with a male-like gonadal transcriptome exhibited down-regulation of both key profemale genes such as cyp19a1a and vtg5 as well as downregulation of profemale pathways such as oocyte meiosis, progesterone-mediated oocyte maturation, canonical Wnt signaling (28,53), and Fanconi anemia (26). Another profemale pathway, the NF-κB pathway, involved in blocking apoptosis through an inflammatory process during ovarian development (27), was not affected, although some of its genes (e.g., bcl2, nfkb, tradd) were down-regulated.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In fish, masculinization by elevated temperature usually involves down-regulation of profemale genes, such as cyp19a1a and foxl2, and up-regulation of promale genes, such as dmrt1 or amh (8)(9)(10)(11)(12)(13)(14). In accordance with this general pattern, the FHT2 females with a male-like gonadal transcriptome exhibited down-regulation of both key profemale genes such as cyp19a1a and vtg5 as well as downregulation of profemale pathways such as oocyte meiosis, progesterone-mediated oocyte maturation, canonical Wnt signaling (28,53), and Fanconi anemia (26). Another profemale pathway, the NF-κB pathway, involved in blocking apoptosis through an inflammatory process during ovarian development (27), was not affected, although some of its genes (e.g., bcl2, nfkb, tradd) were down-regulated.…”
Section: Discussionmentioning
confidence: 66%
“…In contrast, ovarian differentiation continues in the future females (25), with an increase in cytoplasm volume of oocytes at around 60 dpf. Transcriptomic analysis of zebrafish sex differentiation has shown that apoptosis (24), activated by the p53 signaling pathway (26), is required for testis differentiation, whereas up-regulation of the canonical Wnt and NF-κB signaling pathways is needed for ovarian differentiation (27,28).…”
mentioning
confidence: 99%
“…Indeed, other wnt genes have been shown to display a sex-specific expression at different stages of development in the rainbow trout (Nicol & Guiguen 2011). Moreover, transgenic inhibition of wnt signaling results in male-biased sex ratios, suggesting that Wnt signaling is a conserved key pathway during gonadal differentiation in zebrafish (Sreenivasan et al 2014). In medaka (Oryzias latipes), Rspo1 and Rspo2 are prominently expressed in both germ cells and somatic cells (Zhou et al 2012).…”
Section: Teleost Fishesmentioning
confidence: 99%
“…Gene ontology terms of these differentially expressed genes included biological processes such as reproduction (GO:0000003), sexual reproduction (GO:0019953), the reproductive process (GO:0022414), the reproductive developmental process (GO:0003006), gamete generation (GO:0007276), fertilization (GO:0009566) and the reproductive cellular process (GO:0048610). Twenty-one of these transcripts were also shown to have sex-related roles or differential expression in the gonads in previous studies (Table 4) [8,[30][31][32][33][34]. This finding showed that the assembled transcriptome could be reliably used as a reference for differential expression analyses.…”
Section: Application Of the Asian Seabass Transcriptome For Rna-seq Ementioning
confidence: 52%